Pengaruh Kompetensi dan Lingkungan Kerja terhadap Kinerja Karyawan di KSU - Hidayah, Nuril; Jatmiko, Udik; Fuad, A. Zaky; Salim, Helmi Agus (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study examines the sustainable economic transformation in rural Indonesia, focusing on Warujayeng Village, East Java, during the post-pandemic era. The research addresses how rural communities integrate traditional practices with modern innovations to achieve economic resilience, challenging conventional modernization paradigms. Employing a qualitative approach with participatory observation, in-depth interviews, and document analysis, the study identifies three adaptation phases: selective resistance, limited experimentation, and hybrid practice institutionalization. Key findings reveal that 72% of traditional traders adopted digital platforms while maintaining interpersonal transactions, and polyculture farming systems showed 23% greater resilience than monocultures during crises. The study introduces the concepts of